THE EFFECT OF EXPERIENTIAL MARKETING AND STORE ATMOSPHERE ON CUSTOMER LOYALTY (STUDY ON TM 100 COFFEE CUSTOMERS) - Cahyadi, Willy (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
This study aims to determine the effect of experiential marketing and store atmosphere on customer loyalty (study on TM 100 coffee customers). This type of research is quantitative research with an associative approach, that is, the relationship between two or more variables. This study used a sampling technique using the slovin formula with an error rate of 10%. The number of samples taken was 75 respondents who were consumers of TM 100 Coffee. The test equipment used is instrument test, classical assumption test, and hypothesis test. The results of this study show that the experiential marketing variable (X1) has no partial effect on customer loyalty (Y) in TM 100 Coffee. The store atmosphere variable (X2) partially affects customer loyalty (Y) on TM 100 Coffee.